Блокчейн-технології в управлінні комунікаціями інфраструктурних проектів - Литвиненко, Дмитро Петрович; Малєєва, Ольга Володимирівна; Єлізєва, Аліна Володимирівна (Radìoelektronnì ì komp'ûternì sistemi (Online), 2021)
The subject of research in the article is the processes and technologies of communication management of infrastructural projects. The possibilities of using blockchain technology in the field of project management are considered. The goal of work: improving the information security of infrastructure projects. The risks of stakeholder communications will be reduced by increasing the security of data access and reducing the time for their processing, which in turn will provide more flexible project management. The tasks of the work: to analyze the current state of development of blockchain technology and conduct a comparative analysis of technology and modern generally accepted management methods, give examples of implementation, determine the advantages of blockchain technology in modern conditions; analyze the benefits of using smart contracts in communication management, apply the smart contract life cycle model in an infrastructure project. Research methods: systems analysis, design approach, structural modeling, instrument Geth, programming language Solidity. The following results were obtained. The main directions of development and implementation of blockchain technology are characterized, examples of the use of blockchain technology in various industries are collected and analyzed, the main advantages and disadvantages of the technology are identified, a comparative analysis of blockchain technology and classical project management methods is carried out, the possibilities of using blockchain technology in the field of project management are described, the main the possibility of implementing reasonable contracts, the advantages and disadvantages of reasonable contracts are identified, the advantages and disadvantages of the instrument of reasonable contracts are analyzed in comparison with the traditional approach. The smart contract life cycle model presents the creation stages, installation to the blockchain contract managing, and contract completion. Provided an example of the smart contract used for the complex financial project, which reduced the risk of project failures. Conclusion. The scientific novelty of the obtained results is in the improvement of the project management life cycle model through the further development of the smart contract model. This allows to increase information security, reduce possible risks and guarantee the implementation of an infrastructure project through the use of blockchain technology in comparison with classical project management methods.